A modified mouse model for observational fear learning and the influence of social hierarchy - Shi, Tianyao; Feng, Shufang; Shi, Wenlong; Fu, Yuan; Zhou, Wenxia (Frontiers in Behavioral Neuroscience, 2022)
Background: Indirectly experiencing traumatic events either by witnessing or learning of a loved one’s suffering is associated with the highest prevalence rates of epidemiological features of PTSD. Social species can develop fear by observing conspecifics in distress. Observational fear learning (OFL) is one of the most widely used paradigms for studying fear contagion in mice. However, the impact of empathic fear behavior and social hierarchy on fear transfer in mice is not well understood. Methods: Fear emotions are best characterized in mice by using complementary tests, rather than only freezing behavior, and simultaneously avoiding behavioral variability in different tests across time. In this study, we modified the OFL model by implementing freezing (FZ), open field (OF) and social interaction (SI) tests in a newly designed experimental facility and applied Z-normalization to assess emotionality changes across different behaviors. Results: The integrated emotionality scores revealed a robustly increased emotionality of observer mice and, more importantly, contributed to distinguishing susceptible individuals. Interestingly, fos positive neurons were mainly found in the interoceptive network, and mice of a lower social rank showed more empathy-like behaviors. Conclusion: Together, our findings highlight that combining this experimental model with the Z-scoring method yields robust emotionality measures of individual mice, thus making it easier to screen and differentiate empathic fear-susceptible from -resilient mice and refining the translational applicability of these models.